Network labour and non-elite knowledge workers in China. (1st October 2010) - Jack Linchuan Qiu
Abstract : This paper offers a preliminary analysis of Chinese non-elite knowledge workers, their use of information technologies as tools of employment as well as worker organisation, and the emergent process of network labour formation. It opens by presenting a conceptual framework for understanding non-elite knowledge workers, their social contexts, types, and the interrelationships among these types, paying special attention to new types of digital work (call centres, SMS authoring, and online game gold farming), their process of emergence and patterns of spatial distribution. It then sketches out the main linkages between grassroots workers' groups in mainland China and labour organisations outside showing that, even though bottom-up transnational labour organisation is still quite limited at the present stage, informal networking through new digital tools is full of potential. The paper concludes with a discussion of the implications for a new informational politics.